Selected Essays - Dockrell, W. B. Lobban, J.H 1929-; Scottish Council for Research in Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Five essays selected from 70 papers and books spanning 30 years in the publishing life of W. Bryan Dockrell are presented. The essays concentrate on three themes within the field of educational evaluation--attainment, assessment, and reporting. Perspectives and practices in different countries are provided. The essays include: (1) "The Contribution of National Surveys of Achievement to Policy Formation"; (2) "On Intelligence"; (3) "Assessment in the Classroom"; (4) "Reporting Assessments of Pupils' Attitudes and Personality"; and (5) "Certifying School Graduates." (TJH)
Availability: The Scottish Council for Research, 15 St. John Street, Edinburgh EH8 8JR Scotland.
Microfiche.
Keywords: Academic Achievement; Classroom Research; Cross Cultural Studies; Educational Assessment; Educational Policy; Elementary Secondary Education; Essays; Foreign Countries; Graduation Requirements; Intelligence Tests; National Surveys; Personality Assessment; Policy Formation; Student Attitudes; Student Certification; Student Evaluation; Dockrell (W Bryan); Collected Works, General; Reports, Research